Curriculum making across sites of activity in upper secondary school vocational education and training: A review of the research in Sweden - Daniel Alvunger (International Journal for Research in Vocational Education and Training (IJRVET), 2024)
Purpose: This paper presents a qualitative systematic review of Swedish research on vocational education and training (VET) at the upper secondary school level over the past 20 years. The review is based on a theoretical model on curriculum making as social practice that may serve as model for comparative studies between countries. By introducing the model, the ambition is to open for new perspectives on VET curriculum in policy and practice. Questions regarding key themes and the interplay of discourses and processes across multiple sites in the education system have not been addressed in previous systematic reviews of Swedish VET research. Methods: The methodological approach in the present paper is a qualitative systematic research review with an integrative and interpretative purpose and research design. The qualitative review is based on the conceptual model of curriculum making as social practice, seeking to capture the inherent complexity and porous boundaries of education systems and movements of ideas, discourses and actors between sites of activity. The model is used for mapping the research, and a content analysis for identifying main themes and emphases and exploring and discussing the potential gaps that may inform future international research studies. Findings: The results show that the research is focused on the micro and nano sites of curriculum making, with connections to macro site activities of national curriculum policy enactment. Research focusing on the macro site of activity has an emphasis on national policy and policymaking regarding the relationship between academic and vocational knowledge/programmes and apprenticeship and employability. In the micro and nano sites of activity - which comprise the majority of the research - the main themes are vocational knowing and identity, teaching, learning and assessment practices and work-based learning. Conclusion: An observation is the absence of principals and middle leaders as actors and informants in the studies. There is little evidence of actors moving between sites of activity and the meso site of activity only comprise a very small part of the research. In this respect, there is a potential gap to be explored, not least regarding how local curricula and syllabi are made and shaped in terms of the influence of representatives from local authorities, companies, trade unions, employer associations, universities and regional agencies. Curriculum making as social practice has the potential to be used for comparative international studies and as a framework that takes national differences in VET education systems into account.
Keywords: 330; Curriculum Making; VET; Vocational Education and Training; Qualitative Research Revie